The (PATAN)-CheY-Like Response Regulator PixE Interacts with the Motor ATPase PilB1 to Control Negative Phototaxis in the Cyanobacterium Synechocystis sp. PCC 6803. (17th October 2019) - Jakob, Annik; Nakamura, Hiroshi; Kobayashi, Atsuko; Sugimoto, Yuki; Wilde, Annegret; Masuda, Shinji
Abstract: The cyanobacterium Synechocystis sp. PCC 6803 can move directionally on a moist surface toward or away from a light source to reach optimal light conditions for its photosynthetic lifestyle. This behavior, called phototaxis, is mediated by type IV pili (T4P), which can pull a single cell into a certain direction. Several photoreceptors and their downstream signal transduction elements are involved in the control of phototaxis. However, the critical steps of local pilus assembly in positive and negative phototaxis remain elusive. One of the photoreceptors controlling negative phototaxis in Synechocystis is the blue-light sensor PixD. PixD forms a complex with the CheY-like response regulator PixE that dissociates upon illumination with blue light. In this study, we investigate the phototactic behavior of pixE deletion and overexpression mutants in response to unidirectional red light with or without additional blue-light irradiation. Furthermore, we show that PixD and PixE partly localize in spots close to the cytoplasmic membrane. Interaction studies of PixE with the motor ATPase PilB1, demonstrated by in vivo colocalization, yeast two-hybrid and coimmunoprecipitation analysis, suggest that the PixD–PixE signal transduction system targets the T4P directly, thereby controlling blue-light-dependent negative phototaxis. An intriguing feature of PixE is its distinctive structure with a PATAN (PatA N-terminus) domain. This domain is found in several other regulators, which are known to control directional phototaxis. As our PilB1 coimmunoprecipitation analysis revealed an enrichment of PATAN domain response regulators in the eluate, we suggest that multiple environmental signals can be integrated via these regulators to control pilus function.